2023
DOI: 10.1111/jdv.18825
|View full text |Cite
|
Sign up to set email alerts
|

Brodalumab in plaque psoriasis: Real‐world data on effectiveness, safety and clinical predictive factors of initial response and drug survival over a period of 104 weeks

Abstract: Background Brodalumab, a fully human IgG2k antibody blocking the receptor of IL17, is characterized by a rapid onset of action with high skin clearance rates in clinical trials. Since setting PASI90/100 or absolute PASI ≤ 3 as treatment goals have become attainable, evaluating the effectiveness and safety profile of biologic agents, such as brodalumab, in a real‐world setting is essential. Objective The aim of this study was to evaluate the effectiveness and safety profile of brodalumab over a period of 104 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…To our knowledge, this is the first description of a PsO patient group who switched from an originator biological to another originator from the same group, other than a biosimilar, not because of inefficacy but as a protocolled procedure, because of health economic reasons. Brodalumab has a 1‐year drug survival rate of 87.6%–89% at 1 year 18,22–24 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first description of a PsO patient group who switched from an originator biological to another originator from the same group, other than a biosimilar, not because of inefficacy but as a protocolled procedure, because of health economic reasons. Brodalumab has a 1‐year drug survival rate of 87.6%–89% at 1 year 18,22–24 …”
Section: Discussionmentioning
confidence: 99%
“…Brodalumab has a 1-year drug survival rate of 87.6%-89% at 1 year. 18,[22][23][24] Only a few studies had been performed where patients who failed on Ixekizumab were switched to Brodalumab and had favourable responses. 25,26 These two studies were limited to a duration of 16 weeks, and no drug survival was reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoriasis, an inflammatory skin disease caused by a disorder of the immune system, affects an estimated 1.25 million people. It is characterized by red, itchy, and scaly patches that cause extreme discomfort. The exact cause is still not fully understood as it involves a complex interaction between genetic susceptibility, immune dysfunction, and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we had reported the treatment responses of 75 mg risankizumab for psoriatic patients with inadequate response to 150 mg secukinumab 5 . Multiple factors can contribute to the difference in the treatment response of biologics, including the presence of comorbidities, 6 the number of prior biologics used, 7,8 disease duration 9,10 and body weight. The presence of comorbidities, especially diabetes mellitus (DM), has been shown to affect drug survival of biologics in some studies, 11 but the result seemed to be inconsistent 12 .…”
Section: Introductionmentioning
confidence: 99%